Synthesis of Quinoxalines by a Carbon Nanotube–Gold Nanohybrid‐Catalyzed Cascade Reaction of Vicinal Diols and Keto Alcohols with Diamines. Issue 1 (21st October 2014) - Shah, Nimesh; Gravel, Edmond; Jawale, Dhanaji V.; Doris, Eric; Namboothiri, Irishi N. N.
Abstract A one‐pot oxidation–condensation method for the synthesis of quinoxalines from readily available benzoins or benzhydrols and 1, 2‐phenylenediamines or 2, 3‐diaminopyridine by use of a gold–carbon nanotube nanohybrid as a heterogeneous catalyst is reported. Quinoxalines are formed under mild conditions in air and in excellent yields. The simple and efficient methodology offers a safe and sustainable alternative to conventional acid and/or base‐catalyzed thermal processes.